Handy science : magnetism . ([China] : Educat, 2012)
Discover the wonderful world of magnetism with these 6 exciting experiments. Includes 1 x experiment leaflet, 1 x pouch of iron filings, 1 x plastic bead, 1 x bar magnet, 1 x maze template, 1 x length cotton thread, 2 x ring magnets, 3 x paper clips.